2021
DOI: 10.1016/j.jbc.2021.101110
|View full text |Cite
|
Sign up to set email alerts
|

Valproate activates the Snf1 kinase in Saccharomyces cerevisiae by decreasing the cytosolic pH

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 84 publications
0
10
0
Order By: Relevance
“…The inositol-depleting mood stabilizing drugs lithium and VPA have been shown to activate AMPK (Avery and Bumpus, 2014; Bao et al, 2019; Salsaa et al, 2021). To test the prediction that activation of AMPK by mood stabilizers induces nuclear localization of IP6K1, cells were treated with VPA (1 mM) or lithium (10 mM) for 24 h, and phosphorylated (active) AMPK was measured by Western blot (Willows et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inositol-depleting mood stabilizing drugs lithium and VPA have been shown to activate AMPK (Avery and Bumpus, 2014; Bao et al, 2019; Salsaa et al, 2021). To test the prediction that activation of AMPK by mood stabilizers induces nuclear localization of IP6K1, cells were treated with VPA (1 mM) or lithium (10 mM) for 24 h, and phosphorylated (active) AMPK was measured by Western blot (Willows et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…As a master metabolic regulator, canonical activation of AMPK is mediated by an increase in the AMP/ADP:ATP ratio (Garcia and Shaw, 2017). Interestingly, the inositol-depleting drugs VPA and lithium have been shown to activate AMPK in multiple cell types, and VPA was shown to activate the AMPK homolog Snf1 in yeast (Avery and Bumpus, 2014; Bao et al, 2019; Lee et al, 2020; Salsaa et al, 2021). Furthermore, a recent study identified inositol as a direct allosteric inhibitor of AMPK that acts by blocking activation by AMP (Hsu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Increased glycolytic flux beyond glucose-6-phosphate increases Vma1 activity leading to activation of PKA ( Dechant et al., 2010 ). Recently, valproate has been shown to decrease glycolytic flux resulting in both increased phosphorylation at T210, and decreased Pma1 activity ( Salsaa et al., 2021 ). Here we have shown that decreasing Pma1 activity is a requirement for Snf1 activation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the ATPase activity of Pma1 is the major consumer of cellular ATP. There is plenty of evidence that a decrease in Pma1 activity either by means of pharmacological inhibition [66][67][68] or due to point mutations in the protein leading to partial defects in proton pumping [69] results in an increase in ATP levels. Such increase was also detected in parallel with Pma1 dephosphorylation in cells overexpressing Ppz1 [29], and this finding perfectly fits with the notion that Pma1 is inhibited when Ppz1 levels are high.…”
Section: The Alteration Of Monovalent Cation and Ph Homeostasis Contr...mentioning
confidence: 99%